Biofilm pigments in temporary streams indicate duration and severity of drying. Issue 9 (19th July 2021) - Colls, Miriam; Timoner, Xisca; Font, Carme; Acuña, Vicenç; Sabater, Sergi
Abstract: Increased duration and frequency of droughts under global change may affect both temporary and formerly permanent watercourses. Streambed desiccation, cooccurring solar radiation, and high temperature all may affect the composition and metabolism of photoautotrophic organisms in benthic biofilms. To test these effects, we characterized the composition of pigments when biofilms were exposed to dry conditions, and compared this to pigments measured after flow resumed, as well as to others measured from permanent streams in the same region. This comparison revealed important differences in pigmentary composition based on flow conditions. Active chlorophylls decreased exponentially with the duration and severity of the nonflow period, while chlorophyll degradation products and protective carotenoids increased. Streams experiencing longer and more severe nonflow periods showed the highest dissimilarities in their biofilm pigmentary composition, and this pattern was maintained after flow resumed. Our results pointed to duration of nonflowing periods as the major driver of pigmentary composition, regardless of whether these were interrupted or not by short intervals of water flows. Multivariate changes in pigmentary composition between sampling periods highlighted the influence of the long‐term hydrological history on the relative abundance of different taxonomic groups and their associated pigments. Overall, pigmentary fingerprints are informative of the biofilm capacity to resist water flow interruption and of their ability to recover after water flow returns.